Counter Radicalization Analysis in Efforts to Prevent the Spread of Radical Ideology in Indonesia - Al Tahaj, Reza; Logahan, Jerry M. (UI Scholars Hub, 2019)
Terrorism is a product of the radicalization process, the massive effects of radicalization of IS ideology have resulted in an increase in the threat of terrorism in Indonesia. Factually, the increase in the threat of terrorism in Indonesia can be seen from the large number of victims who fell, namely as many as 35 police died and 67 police were injured in an effort to fight terrorism in the 2014 to 2015. From a total of 171 terrorism acts that have been successfully revealed. During 2000 to 2015, there were 1,064 suspected terrorists who had been arrested. Meanwhile, as many as 408 Indonesians are in Syria to join IS. Indonesia alone there were around 543 people identified as core groups, 246 identified as support groups, and 296 identified as IS sympathizers. The fact that after the establishment of National counterterrorism agency (BNPT) in 2010 which replaced the role of the Counter Terrorism Coordination Desk (DKPT) apparently there were various acts of terrorism and radical radicalization processes in Indonesia. Support and bai'at simultaneously and massively that occurred in various provinces in Indonesia seemed to successfully open our eyes that radicalization as a process is actually being and continues to happen to the people of Indonesia. And this indirectly creates a big question mark about the BNPT prevention program that has been done so far. Therefore, this study was made to find out and conduct an in-depth analysis of how the implementation of counter-radicalization programs carried out by the Directorate of Prevention of BNPT in an effort to prevent the spread of radical ideology in Indonesia. The method in this paper is qualitative research by interview and observation with the stake holders related to counter-radicalization programs carried out by the BNPT and Detachment 88 AT the National Police. The fact finding that the implementation of the counter-radicalization program policy by the Directorate of Prevention of BNPT is carried out with the suitability and compliance between policy direct on and policy implementation in the form of offline or online strategy programs. The offline strategy by the BNPT Prevention Directorate was conducted by procuring programs for seminars, workshops and training activities for BNPT partners, both government agencies, NGOs, and community leaders who were members of the Counter Terrorism Coordination Forum (FKPT). And this is done by BNPT formally, and directly without undercover and third-party intermediaries. The online strategy by the Directorate of Prevention of BNPT is carried out by means of media literacy involving the Media Literacy Task Force, the Peace Media Center (PMD) as managers (coordinators, evaluators, analysts), content formulators, and implementing activities through website, social media, media electronics, and or print media. The content presented contains an image of the government's perspective through BNPT, but now there is a website that is managed by a third party in collaboration with PMD and the Directorate of Prevention of BNPT as an effective counter-narrative media. Even so, this program has just been implemented and certainly requires a process and time to get optimal results. The impact of counterradicalization policies and programs from the Directorate of Prevention of BNPT is still not in accordance with the formulated vision that is